Energy transfer in Aminonaphthalimide-BODIPY dyads upon one and two photons excitation - Collado-Martín, Daniel; Vida-Pol, Yolanda; Nájera-Albendín, Francisco; Pérez-de-Inestrosa-Villatoro, Ezequiel (My University, 2014)
BODIPY dyes are nowadays widely commercialized chromophores that have attracted immense interest as versatile tools in biological chemistry [1]. However, the generally very small Stokes shifts of BODIPY dyes may cause re-absorption or effects from excitation-light scattering, which is a potential drawback for their application, especially in bioimaging. One strategy to bypass this problem is the integration of BODIPY dyes as acceptors in bi- or multichromophoric arrays, some of them qualifying as energy transfer cassettes where donor and acceptor units are electronically non-conjugated [2]. In this communication we present a series of aminonaphthalimide–BODIPY energy transfer cassettes that shown very fast and efficient BODIPY fluorescence sensitization [3]. This was observed upon one- and two-photon excitation, which extends the application range of the investigated bichromophoric dyads in terms of accessible excitation wavelengths. In comparison with the direct excitation of the BODIPY chromophore, the two-photon absorption cross-section of the dyads is significantly incremented by the presence of the aminonaphthalimide donor.The applicability of the new probes in the one- and two-photon excitation mode was demonstrated both in solution and supported on silica nanoparticles, in a proof-of-principle approach in the fluorescence imaging of HeLa cells.
Comunicación oral presentada en las 4 Jornadas Ibéricas de Fotoquímica celebradas en Lisboa, Portugal entre los días 29 de junio a 2 de julio de 2014.
Keywords: Transferencia de energia; Fotoquímica; BODIPY; Energy transfer; Two photons excitation